ANALISIS PENGUKURAN KINERJA BERBASIS VALUE FOR MONEY PADA DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN SANGGAU PERIODE 2013-2014 - B51111181, HERRY SULISTIO (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aimed to (1) know the performance of Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau on period year 2013-2014 seen from economic element, (2) know the performance of Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau on period year 2013-2014 seen from efficiency element, (3) know the performance of Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau on period year 2013-2014 seen from effectiveness element. This research is a descriptive research with the Financial Achievement Realization of Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau which was found in Laporan Akuntabilitas Kinerja Instansi Pemerintah (LAKIP) Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau on period year 2013-2014. The data gathering used was documentation. Analysis data technique used was qualitative descriptive analysis on economic, efficiency, and effectiveness measurement. Based on research result about the performance of Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau from three analyzed programs, they are Increased-quality and Geology Information Access Program, Electricity Development Program, and Mine Development Program, it can be concluded that (1) from economic element on period 2013 and 2014, Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau had been able to conduct the whole programs economically with saving on year 2013 each Rp1.038.300,00, Rp78.724.200,00 and Rp14.123.100,00, and in year 2014 each Rp1.018.730,00, Rp817.089.600,00, Rp5.372.291,00; (2) from efficiency element period year 2013 and 2014, Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau had conducted the whole programs efficiently in year 2013 each 100,54%, 103,56% and 103,26%, and in year 2014 as many as 100,38%, 113,58% dan 103,75% ; (3) from effectiveness element period year 2013, Dinas Energi dan Sumber Daya Mineral Kabupaten Sanggau were able to conduct three programs effectively with effectiveness ratio approaching 100%. Keywords: Economic, Efficiency, and Effectiveness